2018
DOI: 10.3389/fmicb.2018.00897
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus frumenti Facilitates Intestinal Epithelial Barrier Function Maintenance in Early-Weaned Piglets

Abstract: Increased intestinal epithelial barrier function damages caused by early weaning stress have adverse effects on swine health and feed utilization efficiency. Probiotics have emerged as the promising antibiotic alternatives used for intestinal barrier function damage prevention. Our previous data showed that Lactobacillus frumenti was identified as a predominant Lactobacillus in the intestinal microbiota of weaned piglets. However, whether the intestinal epithelial barrier function in piglets was regulated by L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 63 publications
5
57
0
Order By: Relevance
“…Previous studies have reported that oral administration of Lactobacillus changes the structure of the gut microbiota, influencing intestinal mucosal immunity and host metabolism (Valeriano et al, ). For example, administration of L. frumenti JCM 11122 increased the abundance of L. frumenti in the faeces of early weaned piglets, and treatment with L. reuteri ZLR003 significantly altered the microbial diversity and community composition in the intestinal contents of weaned piglets (Hu et al, ; Zhang et al, ). Unexpectedly, Liu et al found no significant changes in the colonic microbiota composition after L. reuteri I5007 administration in suckling piglets (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that oral administration of Lactobacillus changes the structure of the gut microbiota, influencing intestinal mucosal immunity and host metabolism (Valeriano et al, ). For example, administration of L. frumenti JCM 11122 increased the abundance of L. frumenti in the faeces of early weaned piglets, and treatment with L. reuteri ZLR003 significantly altered the microbial diversity and community composition in the intestinal contents of weaned piglets (Hu et al, ; Zhang et al, ). Unexpectedly, Liu et al found no significant changes in the colonic microbiota composition after L. reuteri I5007 administration in suckling piglets (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study also showed that L. plantarum 299v administration significantly changed the proportions of genes for some disease‐associated KEGG pathways such as those for cancers and neurodegenerative diseases. Another Lactobacillus , L. frumenti JCM, was reported to influence disease‐associated metabolic pathways in the intestinal bacterial community (Hu et al, ). Based on the above data, we conclude that changes in the structure of gut microbiotas by L. plantarum 299v may alter the gut‐microbial metabolism and influence intestinal immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry was performed to analyze the expression and distribution of the intestinal tight junction proteins according to a previous study (34). The following antibodies were used in the immunohistochemistry assay: claudin-1 (ab211737; Abcam, Cambridge, MA, USA), occludin (ab216327; Abcam), and zonula occludens-1 (ZO-1) (ab214228; Abcam).…”
Section: Immunohistochemical Analysis Of Intestinal Tight Junction Prmentioning
confidence: 99%
“…The intestinal goblet cell numbers were measured according to a previous study (34). Briefly, colonic and caecal tissues fixed with 4% formaldehyde were embedded in paraffin, and sections (5 mm thickness) were obtained and stained with a PAS stain kit (ab150680; Abcam) according to the manufacturer's protocol.…”
Section: Measurement Of Intestinal Goblet Cell Numbersmentioning
confidence: 99%
“…The primers for real-time quantitative PCR were shown in Table 1. Quantitative real-time PCR was performed with Bio-Rad CFX96 following the procedures previously described in Hu et al (23).…”
Section: Western Blotmentioning
confidence: 99%